Діяльність професійної спілки друкарів «Вогнище» в роки Першої світової війни - Берест, Ігор (Видавництво Львівської політехніки, 2019)
The explosion of the First World War on August 1, 1914 changed the usual rhythm of everyday life. Already in the first months since its inception, a significant part of the lands of Eastern Galicia became a theater of military operations, which also actively influenced the activities of trade unions. Therefore, the article analyzes the situation in Eastern Galicia and the work of the printers' professional union "Vognyshche" during the First World War.
Keywords: war; trade union; society; printers